Impact of roads on biodiversity: a case study from Karekhola rural road in Surkhet district of Nepal - KC, J. K.; Gautam, A. P. (Banko Janakari, 2016)
Loss and degradation of biodiversity is continuing despite the past conservation efforts in Nepal. Out of many potential causes, this study strives to investigate the effects of a road project on biodiversity in the Middle Hills of Nepal. Information about floristic composition was collected from the adjoining community forests using group of 30 circular sample plots, each located at 50 m and 20 m far from the edge of the road. Results provide evidence that rural road projects are contributing to reduction of biodiversity which may be due to the removal of low-yielding timber species near the road-edge. The study also suggests that proximity to road-edge reduces under- storey vegetation which will lead less capable forest to sustain its original biodiversity. However, silvicultural operations have potential to minimize the indirect loss of biodiversity caused by road projects. Banko Janakari A Journal of Forestry Information for Nepal Vol. 26, No. 1, Page: 70-77, 2016